Patient and physical therapist perspectives on spinal manipulative therapy for low back pain and associated clinical outcomes: protocol for a prospective, single-arm intervention study - Jason M Beneciuk; Guogen Shan; Joel Bialosky; Jill R Hayes; Katherine E Buzzanca-Fried; Robert Rowe; Sara Cristello; Trent Harrison; Ryan Vickers (BMJ Open)
Introduction Spinal manipulative therapy (SMT) is a common manual therapy intervention provided by healthcare providers for patients with low back pain (LBP). Responses to SMT are influenced by interactions between the patient and provider. Contextual factors may be specific to the patient, provider, patient-provider relationship or environment in which treatment is provided, with all capable of influencing clinical outcomes. The overall goal of this study is to gain a deeper understanding of contextual factors associated with manual therapy utilisation, perception and outcomes, from both patient and provider perspectives. A better understanding of modifiable contextual factors will inform future studies testing the impact on how SMT is delivered to patients influences clinical outcomes that could potentially advance the clinical science of manual therapy.Methods and analysis A prospective, single-arm study design with follow-up measures assessed up to 26 weeks after initiation of physical therapy for LBP will be used to assess relationships between physical therapy clinical outcomes and contextual factors related to the patient (preference, expectation, pain beliefs, pain associated distress and prior manual therapy experiences), the provider (equipoise, expectation, pain beliefs and clinical experience) and the interaction between the two (therapeutic alliance). Multimodal treatment approach of SMT (required during initial three treatment sessions within a 2week period), exercise and education supported by recent clinical practice guidelines will be encouraged for this study.Ethics and dissemination Ethics approval for the study was obtained from the University of Florida Institutional Review Board. Informed consent is required for physical therapist and patient participant enrolment in this project. The results of this study will be disseminated at professional scientific conferences and submitted for publication in peer-reviewed journals. Reference or approval number: IRB#: IRB202301700Trial registration number NCT06590116.